2021
DOI: 10.1007/s11356-021-16578-4
|View full text |Cite
|
Sign up to set email alerts
|

Protocatechuic acid abrogates oxidative insults, inflammation, and apoptosis in liver and kidney associated with monosodium glutamate intoxication in rats

Abstract: Monosodium glutamate (MSG), a commonly used avor enhancer, has been reported to induce hepatic and renal dysfunctions. In this study, the palliative role of protocatechuic acid (PCA) in MSG-administered rats was elucidated. Adult male rats were assigned to four groups, namely control, MSG (4 mg/kg), PCA (100 mg/kg), and the last group was co-administered MSG and PCA at aforementioned doses for seven days. Results showed that MSG augmented the hepatic (AST and ALT) and renal (urea and creatinine) functions mark… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
(112 reference statements)
0
9
0
Order By: Relevance
“…Although the beneficial effect of plant polyphenols on intestinal health has been studied, the research on PCA and Que regulating cell necrosis is very limited. Only reports from Chen et al who reported that Que inhibited TNF-α induced HUVECs apoptosis in human umbilical vein endothelial cells (HUVECs) after TNF-α stimulation [ 46 ] and Kassab et al who found PCA relived liver and kidney cell apoptosis in rats after monosodium glutamate intoxication [ 47 ]. These results indicate a novel and important role for plant polyphenols in inhibiting cell necrosis, which maybe ultimately contribute to improved barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the beneficial effect of plant polyphenols on intestinal health has been studied, the research on PCA and Que regulating cell necrosis is very limited. Only reports from Chen et al who reported that Que inhibited TNF-α induced HUVECs apoptosis in human umbilical vein endothelial cells (HUVECs) after TNF-α stimulation [ 46 ] and Kassab et al who found PCA relived liver and kidney cell apoptosis in rats after monosodium glutamate intoxication [ 47 ]. These results indicate a novel and important role for plant polyphenols in inhibiting cell necrosis, which maybe ultimately contribute to improved barrier function.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidative mode of action of PCA may refer to the activation of Nrf2 which control and regulate several genes involved in cellular antioxidant protection and detoxification. [ 12,21 ]…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidative mode of action of PCA may refer to the activation of Nrf2 which control and regulate several genes involved in cellular antioxidant protection and detoxification. [12,21] Inflammation during and after MI has been recognized to have a critical role in its pathogenesis. According to earlier studies, ISO injection provoked substantial increases in TNF-α, IL-1β, and NF-κB in the cardiac tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the culture of blastocysts in medium containing 5.0 mM glutamate, significantly reduces blastocyst cell numbers, especially in the ICM [ 7 ]. Since MSG intoxication causes apoptosis in rat liver and kidney [ 32 ], we suggest that excess glutamate also causes reduction in ICM cell number, in part, via apoptosis in the blastocyst ( Figure 1 ). The likely need for carefully regulated glutamate production and signaling in the blastocyst ICM are illustrated in Figure 1 .…”
Section: How Might Exogenous Glutamate Overwhelm This Regulated Way O...mentioning
confidence: 99%